Country and gender differences in the association between violence and cigarette smoking among youth - Abu Rmeileh, Niveen M. E. (2020)
Background: Exposure to violence in youth may be associated with substance use and other adverse health effects. This study examined cigarette smoking in two middle-income areas with different levels and types of exposure to violence. Methods: Association of exposure to verbal and physical violence with cigarette smoking in the West Bank oPt (2008) and in Jujuy Argentina (2006) was examined using cross-sectional surveys of 14 to 17-year old youth in 7th to 10th grade using probabilistic sampling. Results: Violence exposure rates were more than double for Palestinian girls (99.6% vs. 41.2%) and boys (98.7% vs. 41.1%) compared with Argentinians. The rate of current cigarette smoking was significantly higher among Argentinian girls compared with Palestinian girls (33.1% vs. 7.1%, p < 0.001). Exposure to verbal violence from family and to physical violence increased the odds of current cigarette smoking, respectively, among Argentinian girls (aOR = 1.3, 95% CI = 1.0–1.7; aOR = 2.5, 95%CI = 1.7–3.8), Palestinian girls (aOR 2.2, 95%CI = 1.1–2.4; aOR = 2.0, 95%CI = 1.1–3.6) and Argentinian boys (aOR = 1.5, 95%CI = 1.1–2.0; aOR = 2.2, 95%CI = 1.6–3.0), but not among Palestinian boys. Conclusion: Findings highlight the importance of producing context and gender specific evidence from exposure to violence, to inform and increase the impact of targeted smoking prevention strategies.